JEWELLERY FORMING TECHNIQUES DEPICTION IN A METAL MURAL: KNUST LANDMARKS - Panin K.B., Owusu; Stephen, Alale; Samuel, Awuni; Frank P.M., Nti; Freeman T., Osabutey (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
The complicated nature of this various technique limits jewellers and metalsmiths in the kind of design and size of works that they normally produce, which is mainly jewellery and jewellery- scaled items. This is as a result of artisan’s inability to introducing modern production methods and design in their practice as well as lack of improving the aesthetic appeal of products by incorporating jewellery forming techniques in a metal sculpture mural. Various jewellery forming techniques were reviewed; further reviews were also conducted on landmarks in KNUST that can be incorporated in the metal sculpture mural to enhance their beauty. A qualitative research approach was employed making use of descriptive and studio-based research designs for the study. Observations were the tool used in gathering data. The results of this study indicate that by selecting the appropriate materials and workshop practices, it is possible to produce murals using the jewellery forming techniques irrespective of the design and size of the object. It is therefore recommended that jewellers, sculptors or metalsmiths in general are to establish and to combine other jewellery or metalsmithing techniques (such as granulation, welding, casting, electroforming, etc.) to produce artefacts other than jewellery-scale items.